Oxygen uptake of wave surfers and complementary parameters in front crawl and surfing-paddling tests - Godoy, D. F.; Cadore, E. L.; Feitosa, W. G.; Correia, R. D. A.; Castro, F. A. D. S. (The Journal of Strength and Conditioning Research, 2021)
The aims of this systematic review were to (a) examine the reliability of the reactive agility tests and (b) analyze the discriminatory validity of the agility tests. A literature search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We explored PubMed, SPORTDiscus, and Cochrane Plus databases looking for articles about agility in team sports. After filtering for article relevance, only 42 studies met the inclusion criteria; 37 of which assessed the reliability of agility tests and 22 assessing their validity. Reliability showed a high intraclass correlation coefficient (ICC) in almost all studies (range 0.79-0.99) with the exception of 2 studies. In addition, other studies also assessed the reliability of decision time (ICC = 0.95), movement time (ICC = 0.92), and decision accuracy (ICC = 0.74-0.93), all of which exhibited acceptable reliability. Furthermore, these data show high discriminatory validity, with higher performance level players being faster than lower performance level players (mean = 6.4%, range = 2.1-25.3%), with a faster decision time (mean = 23.2%, range = 10.2-48.0%) with the exception of 1 study, and better decision accuracy (mean = 9.3%, range = 2.5-21.0%). Thus, it can be concluded that reactive agility tests show good reliability and discriminatory validity. However, most agility tests occur in simple contexts whereby only 2 possible responses are possible. Therefore, future research should consider creating more specific and complex environments that challenge the cognitive process of high-level athletes.